POLYCYSTIC OVARY SYNDROME IN NILE TILAPIA, Oreochromis niloticus - BERTIPAGLIA, K. S. S.; SILVA, A. H.; LOPES, J. W.; GROTH, A.; MORAES, A. C.; FOZ, E. P.; BELO, M. A. A.; PRADO, E. J. R. (Ars Veterinaria, 2018)
This study presented a case report of a female of Oreochromis niloticus in the reproductive age. In the clinical analysis, the animal showed intense abdominal distension, severe cachexia, retraction of the eyeball and lethargic behavior. At the necropsy, it was observed the presence of neoplastic mass in the peritoneal cavity which presented smooth surface, circular appearance, soft consistency and reddish-blackened focal regions. There was the formation of multiple cysts, which presented a yellowish-green liquid content in the cut. In the histopathological examination, multiple dilatations were observed, filled with amorphous eosinophilic material with a delicate fibrocolagenous wall, as well as detachment of the granulosa and theca cells. The presence of macrophage infiltrates with hemosiderin pigments was also observed. The macroscopic and microscopic findings confirm the diagnosis of polycystic ovarian syndrome; however the causes of this cystic disease were not understood.